From Pandemic to Endemic–Redefining Excellence in Thoracic Surgery Service Delivery - Leow, Lowell; Tam, John Kit Chung (Frontiers in Surgery, 2021)
Covid-19 has touched all corners of the globe and impacted our lives in more ways than one. Thoracic surgeons are frontliners impacted in both our professional and personal capacities. In this commentary we discuss the impact that Covid-19 has had on thoracic surgery as a practice highlighting the discrepant impact upon developed and developing countries, the state of affairs of the “new normal” that we live in and the challenges ahead as we transition from pandemic living to endemic living alongside Covid-19. We need to evolve as the virus does and keep abreast of the latest developments to continue providing excellent care to our patients. While the challenges brought about by the Covid-19 pandemic are unprecedented in this generation, it can bring forth tremendous opportunities for us to redefine excellence in thoracic surgery service delivery in this endemic times.